Bone-targeted agent treatment patterns and the impact of bone metastases on patients with advanced breast cancer in the United States. (4th March 2019) - Henry, David; von Moos, Roger; Body, Jean-Jacques; Rider, Alex; De Courcy, Jonathan; Bhowmik, Debajyoti; Gatta, Francesca; Hechmati, Guy; Qian, Yi
Abstract: Objective: Bone metastases are common among patients with advanced breast cancer, putting patients at increased risk of skeletal-related events (SREs). This study described impact of bone metastases, utilization of bone-targeted agents (BTAs) and physicians' decision processes for BTA use in advanced breast cancer. Methods: Data were collected using the Adelphi Breast Cancer Disease-Specific Programme in the United States. Physicians completed a detailed record for eligible patients (women ≥18 years, with stage IIIB–IV breast cancer). Results: Data available from 1276 patients with advanced breast cancer included 485 (38%) with bone metastases. Most (80%) reported pain at bone metastasis diagnosis; of those reporting pain, 55% reported moderate to severe pain. Among patients with bone metastasis, 69% received a BTA. Reasons for initiating BTAs were bone pain (32%) and an estimated high risk of SREs (25%). Reasons for not treating with BTAs were very recent diagnosis (37%), poor Karnofsky performance status (14%), perceived low risk of SREs (11%) and short life expectancy (11%). Zoledronic acid (48%) and denosumab (42%) were commonly used BTAs; the main reasons for initiating BTA treatment were long-term safety (28% and 32%, respectively) and efficacy in delaying SREs (15% and 31%, respectively). The analysis was not adjusted for age or other possible confounders. Conclusion: Bone pain is a common and sometimes severe symptom of bone metastases in advanced breast cancer and a common reason for initiating BTA treatment. Safety and efficacy were the main factors considered by physicians when selecting BTAs.